Larvicidal effect of pepper plants on Aedes aegypti (L.) (Diptera: Culicidae) - Udom Chaithong (2018)
Ethanolic extracts derived from three species of the Piperaceae (pepper) family, Piper longum L., P. ribesoides Wall., and P. sarmentosum Roxb. ex Hunt., were evaluated for efficacy against early 4th instar larvae of Aedes aegypti mosquitoes using larvicidal bioassays. The highest larvicidal efficacy was established from P. longum, followed by P. sarmentosum and P. ribesoides, with LC50 values of 2.23, 4.06, and 8.13 ppm, respectively. Observations of morphological alterations on treated 4th instar larvae revealed that most organs, except anal papillae, had a normal structural appearance that was similar to controls. Under light microscopy, the internal structures of anal papillae in the treated larvae showed shrinkage, while the external features were normal in appearance. Ultrastructural studies, however, clearly demonstrated external destruction, with extensive damage and shrunken cuticle of the anal papillae. The structural deformation of anal papillae probably led to their dysfunction, which may be intrinsically associated with the death of the larvae. This study affords some evidence regarding the action site of the pepper extracts and suggests their potential in developing new types of larvicides used for mosquito control.